To study the efficacy of sabina, cimicifuga and thalaspi bursa in management of cases of dysfunctional uterine bleedings - Aphale, Parth; Rajgurav, Atul (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: Abnormal uterine bleeding is one of the most common problems among pre and postmenopausal women. Virtually every woman will at some point in her lifetime experiences episodes of bleeding that are perceived as abnormal. Menstrual abnormalities are the cause of discomfort, inconvenience and disruption of healthy social and physical lifestyles among millions of women worldwide. Dysfunctional uterine bleeding is an abnormal bleeding from uterus in the absence of an organic pathology to account for. It commonly occurs in reproductive and perimenopausal age groups. When no systemic or local pelvic cause is evident to the clinician, histopathological examination of the endometrial biopsies remains the only alternative to reach the diagnosis. The following study intends to find out the incidence of various etiopathological factors in cases of dysfunctional uterine bleeding and to study the efficacy of Homoeopathic Medicines in cases of DUB. Methods: 30 cases fitting the case definition were studied. Female patients above 35yrs. age showing abnormal bleeding from the uterus without any underlying pathology were selected for the study. Pregnant women, females below 35yrs., showing abnormal finding on USG were excluded from the study. Criteria for assessment were laid down and scoring was done and analyzed. Results: Scoring was done before treatment and after treatment, t- test was applied. Null and alternative hypothesis were laid down. From the value of t-test, we reject the null hypothesis and accept the alternative hypothesis. Conclusions: Homoeopathic medicines Sabina, Cimicifuga and Thalaspi Bursa were found effective in management of cases of DUB.